2019
DOI: 10.1177/0165025419877971
|View full text |Cite
|
Sign up to set email alerts
|

Life after childhood bullying: Body image development and disordered eating in adulthood

Abstract: Studies have demonstrated that being bullied in childhood may have long-term associations with lower psychological well-being in adulthood. However, although bullying incidents frequently target the victim’s body and appearance, research has overlooked studying victims’ long-term body image development and risk of engaging in disordered eating later in life. This 14-year longitudinal research project examined childhood bullying in relation to body image development and disordered eating in emerging adulthood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Thus, the current findings should not be taken as reason to not intervene against negative peer relations among early maturers in early adolescence. Rather, professionals and policy makers need to be aware of the social risks associated with early puberty among both girls and boys and future research is needed to understand whether the negative peer experiences in early adolescence among early maturers translates into problematic outcomes in other domains, for instance, self-esteem or delinquency (Gattario, Lindwall, & Frisén, 2020; Wong & Schonlau, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current findings should not be taken as reason to not intervene against negative peer relations among early maturers in early adolescence. Rather, professionals and policy makers need to be aware of the social risks associated with early puberty among both girls and boys and future research is needed to understand whether the negative peer experiences in early adolescence among early maturers translates into problematic outcomes in other domains, for instance, self-esteem or delinquency (Gattario, Lindwall, & Frisén, 2020; Wong & Schonlau, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to a myriad of factors, including body changes during puberty, an appearance-focused peer environment (e.g., appearance-based teasing, comparisons, role modeling dieting behaviors), and the importance placed on peer acceptance (Harter, 2012;Voelker, Reel, & Greenleaf, 2015). For many girls, negative body image increases while positive body image decreases during adolescence (Bucchianeri, Arikian, Hannan, Eisenberg, & Neumark-Sztainer, 2013;Eisenberg, Neumark-Sztainer, & Paxton, 2006), and these body image changes tend to persist into adulthood (Holmqvist Gattario, Lindwall, & Frisén, 2020;Wang et al, 2019). Critically, negative body image is associated with disordered eating, depressive symptoms, and low self-esteem in adolescence (Choi & Choi, 2016;Rodgers et al, 2020) and adulthood (Holmqvist Gattario et al, 2020;Sharpe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For many girls, negative body image increases while positive body image decreases during adolescence (Bucchianeri, Arikian, Hannan, Eisenberg, & Neumark‐Sztainer, 2013; Eisenberg, Neumark‐Sztainer, & Paxton, 2006), and these body image changes tend to persist into adulthood (Holmqvist Gattario, Lindwall, & Frisén, 2020; Wang et al, 2019). Critically, negative body image is associated with disordered eating, depressive symptoms, and low self‐esteem in adolescence (Choi & Choi, 2016; Rodgers et al, 2020) and adulthood (Holmqvist Gattario et al, 2020; Sharpe et al, 2018). Therefore, targeting contexts that exacerbate pressures of this developmental period and negatively impact adolescent body image could mitigate the short‐ and long‐term health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study conducted in Sweden found that frequent childhood victimization correlated positively with disordered eating in adulthood, suggesting that being bullied is not only associated with disordered eating but can be a risk factor for it. 16 …”
Section: Discussionmentioning
confidence: 99%